2012
DOI: 10.1615/intjmedmushr.v14.i4.30
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Contents of Several Bioactive Components in Fruiting Bodies and Mycelia of Culinary-Medicinal Mushrooms

Abstract: Mushrooms have been consumed for thousands of years, and several bioactive components were found therein, including lovastatin, γ-aminobutyric acid (GABA) and ergothioneine. The study reported herein was to analyze these three bioactive components in 15 fruiting bodies and 9 mycelia of 19 species of mushrooms from genera Agaricus, Agrocybe, Auricularia, Boletus, Ganoderma, Hypsizygus, Inonotus, Lentinus, Morchella, Pleurotus, Tremella, Termitomyces, and Volvariella. The results show that Hypsizygus marmoreus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…Specifically, AMRL 52 and AMRL 63 mycelia achieved the highest TP content of 18.4% and 15.4% of dried biomass in PP and WG–PP, respectively. Previous studies have identified the bioactive compounds [60] deriving from Morchella mushrooms, showing that their functional properties are related to beneficial effects on human health [20,21,61]. The present results demonstrate the perspective for the production of bioactive compounds, such as glucosamine and polysaccharides, from Morchella sp.…”
Section: Resultssupporting
confidence: 69%
“…Specifically, AMRL 52 and AMRL 63 mycelia achieved the highest TP content of 18.4% and 15.4% of dried biomass in PP and WG–PP, respectively. Previous studies have identified the bioactive compounds [60] deriving from Morchella mushrooms, showing that their functional properties are related to beneficial effects on human health [20,21,61]. The present results demonstrate the perspective for the production of bioactive compounds, such as glucosamine and polysaccharides, from Morchella sp.…”
Section: Resultssupporting
confidence: 69%
“…Few studies on the chemical composition of mushrooms Pleurotus salmoneostramineus have been performed whereas the evaluation of their biological activities remains underexplored [15, 28, 29]. In the present study, the fractionating of the organic crude extract of P. salmoneostramineus yielded an antitrypanosomal substance.…”
Section: Discussionmentioning
confidence: 72%
“…For example, the percentage of HMGCR patients with statin exposure ranged from 38 to 63% in US cohorts [8, 34•], was 44% in a European cohort [23], and was only 14–38% in Asian cohorts [22, 49]. Interestingly, statins are present in some foods and dietary supplements including certain types of fungus (like the oyster mushroom) [50], red yeast rice [51], or pu-erh tea [52]. These alternative sources of statins are common in Asian cooking, suggesting the possibility that the weaker association between anti-HMGCR and medical statin exposure in Asian cohorts may be explained by the higher exposure to these other alimentary sources of statins.…”
Section: Etiopathogenesis and Physiopathologymentioning
confidence: 99%